2021
DOI: 10.3390/ijms222312986
|View full text |Cite
|
Sign up to set email alerts
|

An ABA Functional Analogue B2 Enhanced Salt Tolerance by Inducing the Root Elongation and Reducing Peroxidation Damage in Maize Seedlings

Abstract: Salt stress negatively affects maize growth and yield. Application of plant growth regulator is an effective way to improve crop salt tolerance, therefore reducing yield loss by salt stress. Here, we used a novel plant growth regulator B2, which is a functional analogue of ABA. With the aim to determine whether B2 alleviates salt stress on maize, we studied its function under hydroponic conditions. When the second leaf was fully developed, it was pretreated with 100 µM ABA, 0.01 µM B2, 0.1 µM B2, and 1 µM B2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Dietzia natronolimnaes STR1 potentiated salinity tolerance in wheat through upregulation of an ABA signaling cascade and modulation of expression of genes related to ion transport and antioxidant enzymes ( Bharti et al, 2016 ). Exogenous application of a functional analog of ABA alleviated salt stress in maize via enhanced root growth, increased antioxidant enzyme activity, and upregulated expression of aquaporin genes ( Geng et al, 2021 ). We previously found that strain K inoculation led to higher transcription of the ABA-dependent DR29A following salinity stress in Arabidopsis ( Fan and Smith, 2021 ), showing that strain K might prime for ABA-dependent signaling upon salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…Dietzia natronolimnaes STR1 potentiated salinity tolerance in wheat through upregulation of an ABA signaling cascade and modulation of expression of genes related to ion transport and antioxidant enzymes ( Bharti et al, 2016 ). Exogenous application of a functional analog of ABA alleviated salt stress in maize via enhanced root growth, increased antioxidant enzyme activity, and upregulated expression of aquaporin genes ( Geng et al, 2021 ). We previously found that strain K inoculation led to higher transcription of the ABA-dependent DR29A following salinity stress in Arabidopsis ( Fan and Smith, 2021 ), showing that strain K might prime for ABA-dependent signaling upon salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…It achieved this by increasing the activity of antioxidant enzymes and reducing the rate of ROS generation by 16.48%. Furthermore, B2 exhibited the capacity to enhance water absorption by upregulating the expression of the aquaporin gene ZmPIP1 [ 45 ]. Chen et al (2021) demonstrated that alternative splicing is likely to mediate early responses to salt stress during maize seed germination by using RNA-seq and SWATH-MS-based quantitative proteomics [ 46 ].…”
Section: Phytohormonesmentioning
confidence: 99%